Health Care Professionals' Beliefs About Using Wiki-Based Reminders to Promote Best Practices in Trauma Care - Archambault, Patrick Michel; Bilodeau, Andrea; Gagnon, Marie-Pierre; Aubin, Karine; Lavoie, André; Lapointe, Jean; Poitras, Julien; Croteau, Sylvain; Pham-Dinh, Martin; Légaré, France (JMIR Publications, 2012)
Background Wikis are knowledge translation tools that could help health professionals implement best practices in acute care. Little is known about the factors influencing professionals' use of wikis. Objectives To identify and compare the beliefs of emergency physicians (EPs) and allied health professionals (AHPs) about using a wiki-based reminder that promotes evidence-based care for traumatic brain injuries. Methods Drawing on the theory of planned behavior, we conducted semistructured interviews to elicit EPs' and AHPs' beliefs about using a wiki-based reminder. Previous studies suggested a sample of 25 EPs and 25 AHPs. We purposefully selected participants from three trauma centers in Quebec, Canada, to obtain a representative sample. Using univariate analyses, we assessed whether our participants' gender, age, and level of experience were similar to those of all eligible individuals. Participants viewed a video showing a clinician using a wiki-based reminder, and we interviewed participants about their behavioral, control, and normative beliefs-that is, what they saw as advantages, disadvantages, barriers, and facilitators to their use of a reminder, and how they felt important referents would perceive their use of a reminder. Two reviewers independently analyzed the content of the interview transcripts. We considered the 75% most frequently mentioned beliefs as salient. We retained some less frequently mentioned beliefs as well. Results Of 66 eligible EPs and 444 eligible AHPs, we invited 55 EPs and 39 AHPs to participate, and 25 EPs and 25 AHPs (15 nurses, 7 respiratory therapists, and 3 pharmacists) accepted. Participating AHPs had more experience than eligible AHPs (mean 14 vs 11 years; P = .04). We noted no other significant differences. Among EPs, the most frequently reported advantage of using a wiki-based reminder was that it refreshes the memory (n = 14); among AHPs, it was that it provides rapid access to protocols (n = 16). Only 2 EPs mentioned a disadvantage (the wiki added stress). The most frequently reported favorable referent was nurses for EPs (n = 16) and EPs for AHPs (n = 19). The most frequently reported unfavorable referents were people resistant to standardized care for EPs (n = 8) and people less comfortable with computers for AHPs (n = 11). The most frequent facilitator for EPs was ease of use (n = 19); for AHPs, it was having a bedside computer (n = 20). EPs' most frequently reported barrier was irregularly updated wiki-based reminders (n = 18); AHPs' was undetermined legal responsibility (n = 10). Conclusions We identified EPs' and AHPs' salient beliefs about using a wiki-based reminder. We will draw on these beliefs to construct a questionnaire to measure the importance of these determinants to EPs' and AHPs' intention to use a wiki-based reminder promoting evidence-based care for traumatic brain injuries.